Attenuation of Choroidal Thickness in Patients With Alzheimer Disease: Evidence From an Italian Prospective Study. (April 2017) - Trebbastoni, Alessandro; Marcelli, Michela; Mallone, Fabiana; D'Antonio, Fabrizia; Imbriano, Letizia; Campanelli, Alessandra; de Lena, Carlo; Gharbiya, Magda
Abstract : Introduction: To compare the 12-month choroidal thickness (CT) change between Alzheimer disease (AD) patients and normal subjects. Methods: In this prospective, observational study, 39 patients with a diagnosis of mild to moderate AD and 39 age-matched control subjects were included. All the subjects underwent neuropsychological (Mini Mental State Examination, Alzheimer disease Assessment Scale-Cognitive Subscale, and the Clinical Dementia Rating Scale) and ophthalmological evaluation, including spectral domain optical coherence tomography, at baseline and after 12 months. CT was measured manually using the caliper tool of the optical coherence tomography device. Results: After 12 months, AD patients had a greater reduction of CT than controls ( P ⩽0.05, adjusted for baseline CT, age, sex, axial length, and smoking). Discussion: CT in patients with AD showed a rate of thinning greater than what could be expected during the natural course of aging.